High-Grade Supergene Enriched and Exotic Copper Deposits in the Sepon Mineral District, Lao PDR - S Smith (The Australasian Institute of Mining and Metallurgy, 2008)
Several styles of copper (Cu) mineralisation are present at Sepon. Large tonnage, low grade skarn and carbonate replacement massive sulfide mineralisation occur within the metamorphic aureole of Permian-aged rhyodacite porphyry intrusions (RDPs). During exhumation and supergene weathering, this primary mineralisation has been upgraded to form high-grade chalcocite enriched zones up to 50 m thick, which comprises the bulk of Cu resources currently being mined at Sepon. Groundwaters remobilise Cu to form exotic accumulations of malachite that are locally hosted in irregular karsts in carbonate rocks, found up to 1000 m from source mineralisation. Khanong is the largest Cu deposit and recent discoveries have been made at Thengkham South, Thengkham North and Phabing. All deposits have formed by similar processes of mineralisation. However, all differ due to local variations in host rock lithology, structural setting, and hydrological conditions. An EXTENDED ABSTRACT is available for download. A full-length paper was not prepared for this presentation.